Examining the Relationship Between Consumer Sentiment and Stock Price Returns - Harper, Alan; Jin, Zhenhu (Archives of Business Research, 2024)
This study centers on exploring the dynamic relationship between the University of Michigan Consumer Sentiment Index (UMCSI) and the S&P 500 Index, employing both a bivariate regression model and Granger Causality analysis. The aim is to provide deeper insights into how fluctuations in consumer sentiment, as reflected by the UMCSI, impact and are impacted by movements in the S&P 500 Index. Furthermore, Granger Causality analysis is employed to discern the directionality of this relationship. The results indicate that the S&P 500 Index Granger Causes the UMCSI, implying that past values of the S&P 500 Index contain predictive information about future changes in consumer sentiment. This finding suggests that stock market movements can potentially serve as leading indicators of shifts in consumer confidence, offering predictive insights into broader economic trends and consumer behavior.